An Intratumoral Aneurysm and an Extrarenal Synchronous Cystic Tumour in a Case of a Renal Cell Carcinoma - Supun De Silva; Lalani De Silva; Susantha De Silva; Priyani Amarathunga (Case Reports in Urology)
Background. Renal cell carcinoma is a heterogeneous group of malignant tumors originating from the kidney. We report a case of a renal cell carcinoma with two very rare associates, i.e., a large intratumoral aneurysm and a synchronous extrarenal cystic tumor outside the main tumor. Case Presentation. A 31-year-old woman, who presented with painless hematuria and loin pain, was diagnosed to have a large renal mass measuring 15×9×8.5 cm with an intralesional arterial aneurysm measuring 4.5×3.5 cm on radiological examination. During surgery, a separate cystic tumor measuring 5×4.5×4 cm with distinct vascular supply was noted anteromedial to the kidney, in addition to the renal mass. The histology of the main tumor was compatible with t(6:11) type microphthalmia-associated transcription factor (MiT) family translocation RCC. The aneurysm was of venous origin histologically, and a radiologically demonstrable arteriovenous fistula was recognized retrospectively. The extrarenal cyst has also showed similar histology to that of main tumor and had no evidence of a degenerated lymph node. Discussion. Although few cases were reported with various vascular anomalies associated with a renal tumor, this is the first ever case to find an arteriovenous fistula with a secondary venous aneurysm located inside a malignant renal mass. Similarly, no solid RCC is reported to present with an extrarenal malignant cystic nodule. The prognostic and oncological significance of the extrarenal malignant cyst is unclear. Both of these extraordinary features of this case were not properly identified on preoperative imaging. Reviewing the preoperative imaging when pathology reports are available helps to overcome difficulties in making the final diagnosis of complex cases. Conclusion. RCCs can house vascular anomalies like arteriovenous fistula and venous aneurysms and can exist with concomitant extrarenal malignant cystic nodules.